Editors’ Note = Note des rédacteurs en chef - Kealey, Gregory S.; Palmer, Bryan D. (Labour / Le Travail, 2016)
Announces Sean Cadigan's resignation as editor. Bryan Palmer and Gregory Kealey to be interim co-editors until a new appointment is made. Takes note of the Canadian Labour Studies database, an open access bibliography of labour studies resources produced by Laurentian University librarians Desmond Maley and Dan Scott.